(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2021)
ABSTRACT Research has been carried out on the types of birds found in the swamp reclamation area of Palembang city. The purpose of the study was to observe and determine the species of birds found in the former swampy swampy area of Jakabaring Palembang. Sampling was carried out from August to September 2020 using a purposive sampling method by exploring modified locations according to Pranotoet al., (2015) and MacKinnon et al., (2010). The collection was carried out by walking along the research area and determining the places frequented by birds. Birds encountered were identified based on morphological and sound characteristics. The results of the study found 7 orders, 15 families and 26 species. Of the 26 species of birds found, there were 19 bush birds and 7 species of swamp birds. Keywords: Birds, Reclamation, Swamp, species, Jakabaring. Â ABSTRAK Telah dilakukanpenelitianmengenaiJenisburung yang dijumpai pada areal reklamasirawakota Palembang. Tujuanpenelitianmengamati dan menentukanjenisburung yang dijumpai pada areal bekashutan primer berawaJakabaring Palembang. Pengambilan sample dilakukanAgustussampai September 2020 menggunakanmetodepurposifsamplingÂ denganmenjelajahlokasidimodifikasimenurutPranotoet al (2015) dan MacKinnon et al., (2010). Pengambilandilakukandenganberjalansepanjangareal penelitian dan menentukantempat yang seringdikunjungiburung. Burung yang dijumpaidiidentifikasiberdasarkankarakteristikmorfologi dan suara.Hasil penelitiandijumpaiÂ Â Â 7 ordo, 15 familia dan 26 spesies. Dari 26 spesiesburung yang dijumpaiterdapat 19 burungsemakbelukar dan 7 spesiesburungrawa. Kata Kunci :Burung, Reklamasi,Rawa, jenis, Jakabaring.